(3QSGdI aj GdJhMjOs
(3ChdgG (B:s
(3GdeSCdI GdKGfjI hGdYTQhfCeG HYO eeG PcQg GdeTQchf Cfj Cfgj Ydi GdUdGI Ydi GdfHj Udi Gddg Ydjg hSde hHgJGf GaJQGg Ydi GdTjGWjf s
(3BNQgG (B:s
(3ghYHGOI GdCUfGe ef aYdg hJHQA efg QShd Gddg Udi Gddg Ydjg hSde jG YHGO Gddg JacQhG JPcQhG hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B26s
(3GdfSNI HgG MhGTs
(3hQOJ CjVkG JMJ Qbe (B25/430s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG (B(4 D04) s
Keywords: (3GdJhMjO hGdedd hGdfMds